2004
DOI: 10.1002/cbic.200300905
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Polyamines: Simple Access to New Materials with Defined Treelike Structures for Application in Nonviral Gene Delivery

Abstract: Polycationic dendrimers are interesting nonviral vectors for in vitro DNA delivery. We describe a simple approach to the synthesis of dendritic polyamines with different molecular weights and adjustable flexibility (degrees of branching; DB). Both parameters influence the transfection efficiency and the cell toxicity of the polymer. Functionalization of hyperbranched polyethylenimine (PEI) by a two-step procedure generated fully branched pseudodendrimers (analogues of polypropylenimine (PPI) and polyamidoamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 53 publications
1
99
0
2
Order By: Relevance
“…An increasing degree of branching is known to increase the in vitro cytotoxic effects, as well as the haemolysis of erythrocytes [22]. Krämer et al synthesized well-defined pseudo dendrimers based on branched PEI and reported the lowest cytotoxicity for a degree of branching of about 60% [23]. Thus, detailed knowledge about the polymer structure is a prerequisite in order to establish clear structure-function relationships, as well as to optimize cytotoxicity and biocompatibility ( Table 6).…”
Section: Pei: Polymer Structure and Molecular Weightmentioning
confidence: 96%
“…An increasing degree of branching is known to increase the in vitro cytotoxic effects, as well as the haemolysis of erythrocytes [22]. Krämer et al synthesized well-defined pseudo dendrimers based on branched PEI and reported the lowest cytotoxicity for a degree of branching of about 60% [23]. Thus, detailed knowledge about the polymer structure is a prerequisite in order to establish clear structure-function relationships, as well as to optimize cytotoxicity and biocompatibility ( Table 6).…”
Section: Pei: Polymer Structure and Molecular Weightmentioning
confidence: 96%
“…[ 184 ] In vitro DNA transfection of polyplexes in several adherent cell lines indicated that the DB of maximum transfection effi ciency was around 0.6. Further increasing DB resulted in signifi cantly low gene transfection effi ciency as a result of the low molecular fl exibility.…”
Section: Reviewmentioning
confidence: 99%
“…There are numerous nanoscale constructs, assemblies, architectures, and particulate systems being studied as targeted and drug delivery platforms. These include polymeric micelles, dendrimers, virus-derived capsid nanoparticles (NP), polyplexes, and liposomes [1][2][3][4][5]. These nanovehicles do not behave equivalently; their behavior within the biological microenvironment, stability, extracellular and cellular distribution vary with their chemical makeup, morphology and size [6].…”
Section: Introductionmentioning
confidence: 99%